O custeio da previdência do servidor do estado de Mato Grosso e as disputas pelos fundos públicos - Viana, Nelson Corrêa (2014)
This paper discusses pension defrayal of public servant from Mato Grosso state, analyzing risk condition as materiality of social rights in the context of social protection as politics. The state was analyzed as guarantor of protection in the condition of regulator, feature that places it in the context of neoliberalism whose own expression more market and less state, thus social security is in constant challenging tensions for the maintenance of rights already conquered. The fight has not been on more rights, but to avoid losing existing ones. In this sense, the research has qualitative nature with quantitative information, characterizing as an exploratory work in which it is adopt certain assumptions and are guided by them as probable and provisional answer to the problem, the same effect of the hypothesis, however without the characteristic, as a hypothesis, in its exact meaning, to be submitted for verification to be confirmed, as in natural sciences, since dealing with social phenomena not reproducible in the laboratory, because the object is a historical product. The method adopted is the critical dialectic that provides questioning reality from its determinations, not content with linear analysis that only describe the object without relating it to the objective conditions where it materializes, therefore there is a constant search on the essence of praxis. Previously results explicitly a probable scissors effect that can be indicative of risk of pension defrayal in accordance with the assumptions outlined. Data are provisional and require contrastation and adjustments regarding current and constant values. Numbers represent an effort to synthesize of this dialectical plan, but do not mean the “unquestioned truth”, because when disputed could be other numbers than these found in various reports of the organs with bureaucratic control that somehow only legitimate political power that updates itself with its conventions as accounting, for example, which has lately been the object of discussion as "creative accounting". Lastly, it is concluded that in a state governed by neoliberal policies, spaces budgetary claimed by the society has lower expression compared to financial aspects in disputes of public funds by the expressions of Politics with specific interests regulated by state institutions under the supervision of multilateral agencies. This is the probable reason of the changes assayed from the 1988 Constitution in the fundamentals of public servant's pension, whose pretended implicit class privileges are being transferred to the market, whenever possible.